2021
DOI: 10.3390/cancers13030467
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lynch Syndrome and Strategies to Distinguish Lynch-Related Tumors from Sporadic MSI/dMMR Tumors

Abstract: Microsatellite instability (MSI) is a hallmark of Lynch syndrome (LS)-related tumors but is not specific to it, as approximately 80% of MSI/mismatch repair-deficient (dMMR) tumors are sporadic. Methods leading to the diagnosis of LS have considerably evolved in recent years and so have tumoral tests for LS screening and for the discrimination of LS-related to MSI-sporadic tumors. In this review, we address the hallmarks of LS, including the clinical, histopathological, and molecular features. We present recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 286 publications
(532 reference statements)
1
47
0
Order By: Relevance
“…Recently, there has been a rapid hike in the number of reports relating to the linkage between neurodevelopmental disorders and cancer. These include many excellent reviews on the various aspects of neurodevelopmental disorders, such as RASopathy including, e.g., neurofibromatosis type 1 (NF1), Noonan syndrome (NS), Costello syndrome (CS) [e.g., (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)], PIK3CA-related overgrowth spectrum (PROS) [e.g., (24)(25)(26)], ASD [e.g., (27)(28)(29)(30)(31)(32)(33)], cerebral palsy, and more [e.g., (34)(35)(36)(37)], and one uniquely also covering genetically engineered mouse models to study cancer or congenital disorders (38). The linkage between developmental signaling cascades and aggressive central nervous system (CNS) tumors has also been reviewed [e.g., (37,39)].…”
Section: Introduction: the Puzzlesmentioning
confidence: 99%
“…Recently, there has been a rapid hike in the number of reports relating to the linkage between neurodevelopmental disorders and cancer. These include many excellent reviews on the various aspects of neurodevelopmental disorders, such as RASopathy including, e.g., neurofibromatosis type 1 (NF1), Noonan syndrome (NS), Costello syndrome (CS) [e.g., (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)], PIK3CA-related overgrowth spectrum (PROS) [e.g., (24)(25)(26)], ASD [e.g., (27)(28)(29)(30)(31)(32)(33)], cerebral palsy, and more [e.g., (34)(35)(36)(37)], and one uniquely also covering genetically engineered mouse models to study cancer or congenital disorders (38). The linkage between developmental signaling cascades and aggressive central nervous system (CNS) tumors has also been reviewed [e.g., (37,39)].…”
Section: Introduction: the Puzzlesmentioning
confidence: 99%
“…When these errors are not corrected, owing to a flawed MMR system, genomic steadiness is disrupted during DNA replication and recombination-a phenomenon that eventually gives rise to multiple cancer-associated mutations [1][2][3][4][5]. Generally, a deficient MMR (dMMR) system, is triggered by germline (e.g., Lynch syndrome), somatic, and epigenetic changes, which, in turn, result in the inactivation of MMR genes [1,3,[6][7][8][9]. Thus, identifying MMR defective genes is crucial for cancer patient management.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that, although alleles exceeding a certain threshold in length are inherently unstable by their length, common variants in mismatch repair genes can subtly modulate the absolute degree of instability of expanded alleles [15]. Although a similar association of common variants of mismatch repair genes to instability of smaller alleles was not reported, association of rare variants to general microsatellite instability is a relatively rare but wellknown pathological phenotype associated with many cancers, specifically colorectal cancer and other types of cancers collectively known as Lynch syndrome [16]. It was suggested by Guo et al (2016) that repeat expansions can occur if there are both strand slippage and repair escape, while strand slippage occurs more probably with increasing uninterrupted repeat length and repair escape can happen because of a less effective mismatch repair mechanism.…”
Section: Discussionmentioning
confidence: 99%